Using Gamification in the English Classroom: Impact on Motivation and Learning Outcomes - Adrefiza, Adrefiza (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The use of gamification as a teaching strategy in an English language classroom is covered in this study. The goal of this study is to assess how well using gaming features can boost student engagement, motivation, and academic success. The research method used in this article is Library Research, relying on analysis of information sources from various literature, scientific journals, books, research reports, and other related documents that are relevant to this research topic. The findings demonstrated that gamification had a beneficial effect on students' academic performance in English and dramatically raised their participation in class and their enthusiasm to study. The results offer convincing support for using gamification as a cutting-edge and successful teaching strategy in the context of English language instruction. This study adds fresh knowledge about the application of gamification in education and offers useful suggestions for educators and decision-makers to raise the standard of English language instruction in educational settings.